2013
DOI: 10.4161/tisb.25391
|View full text |Cite
|
Sign up to set email alerts
|

Claudins in teleost fishes

Abstract: Teleost fishes are a large and diverse animal group that represent close to 50% of all described vertebrate species. This review consolidates what is known about the claudin (Cldn) family of tight junction (TJ) proteins in teleosts. Cldns are transmembrane proteins of the vertebrate epithelial/endothelial TJ complex that largely determine TJ permeability. Cldns achieve this by expressing barrier or pore forming properties and by exhibiting distinct tissue distribution patterns. So far, ~63 genes encoding for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 95 publications
(223 reference statements)
1
73
0
Order By: Relevance
“…Second, this discrepancy might be partly explained by the function of claudin 15. According to a literature report, claudin 15 creates Na þ -selective paracellular channels, which are associated with Na þ -K þ -ATPase in fish gills [100]. Meanwhile, a dietary protein supplement increases plasma growth hormone concentration in sea bream (Sparus aurata) [101], and McCormick [102] found that growth hormone enhanced the Na þ -K þ -ATPase activity in the gill of Atlantic salmon (Salmo salar).…”
Section: 33mentioning
confidence: 99%
“…Second, this discrepancy might be partly explained by the function of claudin 15. According to a literature report, claudin 15 creates Na þ -selective paracellular channels, which are associated with Na þ -K þ -ATPase in fish gills [100]. Meanwhile, a dietary protein supplement increases plasma growth hormone concentration in sea bream (Sparus aurata) [101], and McCormick [102] found that growth hormone enhanced the Na þ -K þ -ATPase activity in the gill of Atlantic salmon (Salmo salar).…”
Section: 33mentioning
confidence: 99%
“…Fish immunity has also been correlated with the normal structure of the immune organs, which is related to cellular integrity [22,23]. Previous studies in our lab indicate that immune responses could induce ROS production thus cause oxidative damage of fish immune organs after Aeromonas hydrophila infection [24].…”
Section: Introductionmentioning
confidence: 96%
“…Cldns, on the other hand, are essential for tight junction formation, and are primarily responsible for regulating the paracelluallar permeability properties of epithelia. Generally, vertebrates possess over 20 Cldn gene family members (Hewitt, et al, 2006; Günzel and Fromm, 2012), and these have been greatly increased in the genomes of teleost fishes, where some species possess over 50 Cldn genes (Kolosov, et al, 2013). The barrier function that these two protein families contribute to the kidney is essential for its function, and several renal diseases have been associated with mutations in their members (Balkovetz, 2009).…”
Section: Introductionmentioning
confidence: 99%